STATISTICAL STUDY OF THE NATURE OF HAZARDOUS EVENTS WHICH ARE IN THE KHARKOV CITY - , А. Я., Р. І. (Municipal economy of cities. Series: «Economy science», 2017)
Every day in the city of Kharkov there are different kinds of dangerous events. For a successful response to them requires a certain number of forces and means of fire and rescue units. One method that allows determining the required number of capabilities is mathematical modeling. To describe the process of service personnel call the fire and rescue units in the statistical study was conducted flow challenges and proven statistical regularities. It was found that the flow of calls obeys the Poisson distribution and the time intervals between the incoming call distributions exponentially. It was also found that most dangerous of all events occur in Kharkov fire, and that the last three years there in a stable operational environment. The research results will be used in determining the required staffing level fire and rescue units. Keywords: the flow of calls, statistical regularities, the number of fire-rescue units.